Malnutrition in maintenance hemodialysis: Prevalence, patterns, and clinical implications in Bangladesh - Tanjina Rahman; Nasrin Sultana; Shakil Ahmed; Farhana Akter; Marium Sultana; Md Sajjadul Haque Ripon; Harun-ur Rashid (PLoS ONE, 2026)
Malnutrition is a major clinical challenge among individuals receiving maintenance hemodialysis (HD), contributing to increased complications and reduced survival. The burden is particularly pronounced in resource-limited settings, where gaps in nutritional assessment and management persist. This cross-sectional study evaluated the prevalence and determinants of malnutrition among 181 HD patients from four districts in Bangladesh. Based on the International Society of Renal Nutrition and Metabolism (ISRNM) criteria, 42.5% of patients were malnourished, including 10.5% with severe malnutrition, while the Malnutrition Inflammation Score (MIS) identified malnutrition in 72.9% of participants. Patients who reused dialyzers more than twice had significantly higher odds of malnutrition [AOR = 5.8; 95% CI: 1.2–28.7]. Age, body mass index (BMI), and diabetes mellitus were also independently associated with poor nutritional status. These findings underscore the need for strengthened nutritional assessment and early identification of at-risk patients in HD care. Implementing validated diagnostic tools, such as those used in this study, may help reduce disease burden and improve survival outcomes in resource-constrained dialysis settings.